Taming the Lion: How Perceived Worth Buffers the Detrimental Influence of Power on Aggression and Conflict - Weick, Mario; Vasiljevic, Milica; Sedikides, Constantine (Frontiers in Psychology, 2018)
Contrary to conventional wisdom, there is little empirical evidence that elevated power, by default, fuels conflict and aggression. Instead, previous studies have shown that extraneous factors that lower powerholders’ perceived worth, making powerholders feel inferior or disrespected, seem to be necessary to ‘unleash’ power’s dark side and trigger aggression and conflict. However, this past work has largely neglected that power boosts individuals’ perceptions of worth, and as such these variables are not independent. The present research sought to address this oversight, thereby providing a more nuanced account of how perceived worth stifles aggression and conflict tendencies in powerholders. Focusing on self-esteem (Study 1) and status (Study 2) as two interrelated facets of perceived worth, we report primary and secondary data indicating that perceived worth acts as buffer and counters aggression as well as more general conflict tendencies in powerholders. By providing evidence for a suppression effect, the present findings go beyond the moderations identified in prior work and demonstrate that perceptions of worth are critical to understanding the link between power on the one hand, and aggression and conflict on the other. We conclude by discussing the social regulatory function of perceived worth in hierarchical relations.